Hemophagocytic lymphohistiocytosis in the setting of HELLP Syndrome. Issue 12 (5th November 2018) - Sarkissian, Sarmen; Khan, Yasir; Farrell, Daniel; Constable, David; Brem, Elizabeth
Key Clinical Message: Hemophagocytic lymphohistiocytosis (HLH) is a life‐threatening hyper activation of the immune system. Rare cases associated with HELLP syndrome and other similar conditions in pregnancy have been reported. Despite the improved survival rates with etoposide and dexamethasone‐based regimens, HLH remains a challenging disease. Experience in pregnant patients is exceedingly rare. Abstract : Hemophagocytic lymphohistiocytosis (HLH) is a life‐threatening hyper activation of the immune system. Rare cases associated with HELLP syndrome and other similar conditions in pregnancy have been reported. Despite the improved survival rates with etoposide and dexamethasone‐based regimens, HLH remains a challenging disease. Experience in pregnant patients is exceedingly rare.